Vibration Spectroscopy Potential for Beef and Pork Extending Tradition: Design Criteria for Developing of Authentic Banjar Settlements on River Banks in Banjarmasin - Muhammad Alfreno Rizani; Bambang Soemardiono; Sri Nastiti Nugrahani Ekasiwi (Institut Teknologi Sepuluh Nopember, 2020)
Banjarmasin city has the character of settlements along the river that reflects the concept of the authentic Banjar settlements on river banks as a product of Nusantara architecture’s. However, the existence of these settlements began to lose their existence due to changes in life orientation from river culture to landed culture. To restore the existence of these settlements, the government of Banjarmasin city plans to develop these settlements into tourist villages with Banjar culture. This encourages optimization of existing potential by improving the quality of settlements that pay attention to various aspects in the context of the location being developed, such as environmental damage, water quality, and applicable regulations. Although there are many design criteria related to riverbank settlements in Banjarmasin, there are some aspects that have been neglected such as the cultural aspects of urang Banjar which are related to the river and Islam. This has an impact on the quality of settlements that reduce the level of kinship in the Banjar community. By using a force-based framework, the design criteria will be formulated by applying a strategy of extending tradition. The design criteria produced, cover various design aspects that are closely related to activities, order, form, building construction, supporting elements, and circulation patterns to improve the quality of the settlement, so that it can develop into a self-sustaining area with food security, energy sources, and the conservation area of Banjar culture.